Carbohydrate mouth rinse improves 1.5 h run performance: Is there a dose-effect? - Wright, B. F.; Davison, G. (International Journal of Exercise Science, 2013)
There is a substantial body of recent evidence showing ergogenic effects of carbohydrate (CHO) mouth rinsing on endurance performance. However, there is a lack of research on the dose-effect and the aim of this study was to investigate the effect of two different concentrations (6% and 12% weight/volume, w/v) on 90 minute treadmill running performance. Seven active males took part in one familiarization trial and three experimental trials (90-minute self-paced performance trials). Solutions (placebo, 6% or 12% CHO-electrolyte solution, CHO-E) were rinsed in the mouth at the beginning, and at 15, 30 and 45 minutes during the run. The total distance covered was greater during the CHO-E trials (6%, 14.6 ± 1.7 km; 12%, 14.9 ± 1.6 km) compared to the placebo trial (13.9 ± 1.7 km, P 0.05). There were no between trial differences (P > 0.05) in ratings of perceived exertion (RPE) and feeling or arousal ratings suggesting that the same subjective ratings were associated with higher speeds in the CHO-E trials. Enhanced performance in the CHO-E trials was due to higher speeds in the last 30 minutes even though rinses were not provided during the final 45 minutes, suggesting the effects persist for at least 20-45 minutes after rinsing. In conclusion, mouth rinsing with a CHO-E solution enhanced endurance running performance but there does not appear to be a dose-response effect with the higher concentration (12%) compared to a standard 6% solution.